Age Estimation in Children by the Measurement of Open Apices in Teeth: A Study in the Western Indian Population. (30th January 2022) - Manjrekar, Sanjana; Deshpande, Shantanu; Katge, Farhin; Jain, Romi; Ghorpade, Tejaswini
Abstract : In forensic sphere and clinical dentistry, age estimation is a topic of utmost importance. Various techniques are employed in children to determine age; however, dental development has proven to be an appropriate method because of its low variability. Cameriere's method is a widely accepted method of age estimation in children, which is carried out by measuring the projections of open apices and also the heights of developing permanent teeth seen on panoramic radiographs. The aim of this study is to establish a new formula for age estimation in the Western Indian population by measuring the open apices of mandibular teeth using Cameriere's European formula. For this study, we included 311 panoramic radiographs of healthy children living in Western India (Maharashtra, Gujarat, and Goa) aged 4–15 years which were analysed by two independent researchers. Seven left permanent mandibular teeth were assessed for length and width of open apices. Dental maturity was evaluated using measurements of the left seven permanent mandibular teeth ( x i = A i / L i, i = 1, …, 7), the sum of the normalized open apices ( s ), and the number ( N 0) of teeth with complete root formation. A linear relationship between open apices, N 0, age, and other factors was evaluated with the aid of a stepwise multiple regression model. A stepwise linear regression showed that all parameters, gender, s, N 0, and x 5, were significantly associated with age ( R = 85%). No statistically significant difference was found between the predicted and actual chronological age of children in the age group of 4–13 years using the regression equation for the Western Indian population. The present research suggests that the new regression formula developed will be more accurate for age assessment in the Western Indian population.